Solid Phase Extraction and Flame Atomic Absorption Spectrometry for the Determination of Trace Cadmium - Li, Yinke; Huang, Yun; Xu, Yirang; Fan, Peng; Hu, Qiufen; Yang, Guangyu (Asian Journal of Chemistry, 2010)
A method was developed for the separation and preconcentration of Cd(II) ions based on its complex formation with 2-(2-quinolinylazo)- 4-methyl-1,3-dihydroxydibenzene (QAMDHB) loaded on graphitized carbon black as sorbent in a cartridge. The preconcentrated ions were eluted from the cartridge using 2.0 mL of 0.5 mol L-1 HNO3 solution as eluant and then the Cd(II) contents was measured by flame atomic absorption spectrometry. The conditions for preparation of the graphitized carbon black loaded with QAMDHB, pH of sample solution, sample volume, the concentration of washing solution, sample flow-rate through the cartridge, capacity of the modified graphitized carbon black and the effect of matrix on the preconcentration were carefully studied. A preconcentration factor of 500 was achieved under the optimum conditions and the detection limit of the method reached 0.05 μg L-1 for Cd(II). The method was successfully applied to the determination of cadmium(II) in tobacco, soil and water samples. The relative standard deviations were below 3.2 % with recoveries of 91-98 %. The determination results were agreed with that of reference method (ICP-MS method).